Corrosion inhibition effect of 2-N-phenylamino-5-(3-phenyl-3-oxo-1-propyl)-1,3,4-oxadiazole on mild steel in 1 M hydrochloric acid medium: Insight from gravimetric and DFT investigations - Ahmed Alamiery (KeAi Communications Co., Ltd., 2021)
Mild steel corrosion caused by exposure to the hydrochloric acid solution is a major problem affecting a wide range of industries. Iraq is an oil-producing country, and erosion is responsible for a significant amount of total operating expenses and is a potential natural hazard associated with oil production as well as its transportation operations. The novelty of this work is to study the protective response of the synthesized 2-N-phenylamino-5-(3-phenyl-3-oxo-1-propyl)-1,3,4-oxadiazole (NPOPO) which was analysed analytically on the corrosion of mild steel in 1.0 M hydrochloric acid using gravimetric and thermometric techniques. To compare the examined NPOPO electronic structure parameters with the inhibitive performance (IE%) value, the quantum chemical calculations were investigated. Quantum chemical parameters such as Frontier Molecular Orbitals (HOMO and LUMO), the energy gap (ΔE = ELUMO-EHOMO), electronegativity, chemical softness, hardness, and the number of electron transfers (ΔN) were determined and explained. The sites having nitrogen atoms are the most probable positions for coordination covalently with the iron atoms on the surface of mild steel (MS) by donating electrons to unoccupied d-orbitals of Fe atoms. The tested inhibitor obeyed the Langmuir adsorption isotherm model. Thermodynamic parameters such as activation energy (Ea), enthalpy of activation (ΔH∗), the entropy of activation (ΔS∗), and energy of adsorption (ΔGadso) at temperatures 303, 313, 323, and 333 K were evaluated and discussed. The DFT findings as agreeable with experimental outcomes revealed that the investigated NPOPO is an efficient inhibitor for mild steel corrosion in HCl medium.